The Influence of Technology on the Development of Indonesian Language among Youth: A Case Study of Language Use in Short Messages and Social Media - Yanida Bu'ulolo; Boy Damai Zega; Sepi Putra Kasih Lase; Osisio Buulolo (RETORIKA: Jurnal Ilmu Bahasa, 2024)
This study aims to determine the influence of social media use on Indonesian language development among adolescents, the influence of the use of short message platforms on Indonesian language development among adolescents. This study uses a qualitative method with a case study approach. The object of the study is the use of Indonesian by adolescents in text messages and social media. The subjects of this study are adolescents in Indonesia aged 13-19 years. The data collection technique is observation and document collection. The instruments used are (use of language, communication norms and ethics, language structure, social interaction, attitudes and language habits). The results of this study show that the use of Indonesian is more frequent, both orally and in writing. Positive Influence is Increasing the Frequency of Indonesian Speaking, Short message platforms allow teenagers to communicate with many people from various regions in Indonesia. Enriching the Vocabulary, the short messaging platform is colored with various slang, abbreviations, and new terms created by its users. Negative Influences, namely Decline in Language Quality, Use of slang, abbreviations, and new terms that are not standard on short message platforms can reduce the quality of the Indonesian language. Spelling and Grammar Mistakes, Because typing on short messaging platforms is usually done quickly, many teens make spelling and grammar mistakes. This can interfere with adolescents' activities and learning.